On the role of lipid metabolism and lipid peroxidation in the development of retinal disorders in type 2 diabetic rats with myopia (Ukrainian Journal of Ophthalmology, 2025)
Background. There are current data on the role of dyslipidemia and enhanced processes of lipid peroxidation (LPO) in the pathogenesis of diabetic retinopathy (DR). However, pathogenic mechanisms which can explain the link between main parameters of lipid metabolism and development of DR, especially in high myopia, are still understudied. Purpose. To study the parameters of lipid metabolism and lipid peroxidation in blood and retina of streptozotocin-induced diabetic rats with deprivation myopia with a purpose to reveal the pathogenetic features of the development of type 2 diabetes mellitus in the presence of myopia.Material and Methods. The study was performed on Wistar rats. The rabbits were divided into four groups: group 1, 15 rabbits with axial myopia; group 2, 15 rats with diabetes; group 3, 15 rats with myopia and diabetes; 10 intact rats serving as controls. Eyelids of two-week animals (30 rats) were sutured to induce axial myopia, according to Beuerman R.W. et al. The animals were kept under poor light conditions for 14 days. After a fortnight, the sutures were removed. In two weeks, 15 rats with myopia and 15 intact rats were induced type 2 diabetes mellitus (T2DM). T2DM was induced using 5 daily intraperitoneal injections of streptozotocin (15.0 mg per 1 kg). The control rats were kept under natural light condition. The criterion of diabetes onset was an increase in the blood glucose level up to 4.5mmol/L. After two months, the animals were sacrificed under general anesthesia and the eyeballs were enucleated. To assess myopia severity, axial length was measured post mortem using a digital sliding caliper (Topex) with 0.02 mm accuracy. Levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) [16, 17], diene conjugates (DC), and malondialdehyde (MDA) were evaluated in the blood plasma and DC and MDA levels were measured in the retina. The Atherogenic Index (AI) was calculated. Data obtained were processed statistically with the parametric Student-t test using a software program (Statistica).  Results.  Expressed disorders were revealed in lipid metabolism, including increased levels of TC, LDL-C, TG, decreased HDL-C, and those in ratios of metabolic parameters in the blood of STZ diabetic rats with and without myopia. No significant changes in the levels of TC, TG, LDL-C, and HDL-C were noted in the rats with deprivation myopia, which gives evidence that there are no disorders in lipid metabolism in the presence of myopia. Our study revealed no significant difference in lipid profile outcomes between the diabetic-only animals and diabetic animals with myopia. Studying LPO parameters in deprivation myopia showed a statistically insignificant increase in the levels of MDA and DC both in the blood plasma and retina of the myopic rats as compared with controls. STZ-induced diabetes resulted in significant changes in the level of LPO products in the rats’ blood plasma and retina. The MDA level was 3.8 times increased in diabetes (р
Keywords: deprivation myopia; type 2 diabetes mellitus; retina; parameters of lipid metabolism; lipid peroxidation; rats; experiment